Electric Field Tuning Molecular Packing and Electrical Properties of Solution‐Shearing Coated Organic Semiconducting Thin Films. (17th January 2017) - Molina‐Lopez, Francisco; Yan, Hongping; Gu, Xiaodan; Kim, Yeongin; Toney, Michael F.; Bao, Zhenan
Abstract : Recent improvements in solution‐coated organic semiconductors (OSCs) evidence their high potential for cost‐efficient organic electronics and sensors. Molecular packing structure determines the charge transport property of molecular solids. However, it remains challenging to control the molecular packing structure for a given OSC. Here, the application of alternating electric fields is reported to fine‐tune the crystal packing of OSC solution‐shearing coated at ambient conditions. First, a theoretical model based on dielectrophoresis is developed to guide the selection of the optimal conditions (frequency and amplitude) of the electric field applied through the solution‐shearing blade during coating of OSC thin films. Next, electric field‐induced polymorphism is demonstrated for OSCs with both herringbone and 2D brick‐wall packing motifs in 2, 7‐dioctyl[1]benzothieno[3, 2‐b][1]benzothiophene and 6, 13‐bis(triisopropylsilylethynyl) pentacene, respectively. Favorable molecular packing can be accessible in some cases, resulting in higher charge carrier mobilities. This work provides a new approach to tune the properties of solution‐coated OSCs in functional devices for high‐performance printed electronics. Abstract : Tuning the crystal packing of solution‐processed organic semiconductors is a key aspect for achieving high performing printed electronics. An electric field, via dielectrophoresis, is used to tune the crystal packing and modify the electrical performance of solution‐shearing coated organic semiconductors. This method offers an unprecedented degree of freedom in the deposition of crystalline films with controlled molecular packing structure.